Suitability Of Real Cost To Tariff Of INA-Cbgs Of Hypertensive Patients At X General Hospital - Restyana, Anggi; Admaja, Wika (Jurnal Mandala Pharmacon Indonesia, 2024)
Hypertension referred to as the "silent killer". Hypertension is a non-communicable disease that one of the leading causes death in the world. Increasing prevalence of hypertension based on measurements Indonesia in the population aged (18 years by 34.11% with the highest hypertension sufferers in South Kalimantan at 44.13% and the lowest prevalence of hypertension in Papua at 22.22%. In Indonesia, health costs keep increasing due to degenerative diseases. This study aims to determine the Real Cost of hypertensive patients and to determine the difference in Real Cost to the INA CBGs tariff of hypertensive inpatients at General Hospital X Kediri regarding the class of treatment, severity and length of treatment. This study was a descriptive quantitative research using a cross sectional design with retrospective data. The results of the study of the real cost of hospital of hypertensive patients with or without comorbidities at Public Hospital X Kediri was Rp.408,473,500. Meanwhile, the INA CBGs tariff was Rp.211,709,100 so that the difference obtained was negative Rp.196,764,400. The cost consists of class 1 treatment (13 patients) was Rp. (-32,884,800), class 2 (16 patients) was Rp. (-25,262,600) and class 3 (79 patients) was Rp. (-138,617,000). The difference in severity was mild severity (81 patients) of Rp. (-144,856,800), moderate severity (20 patients) of Rp. (-39,647,000) and severe severity (7 patients) of Rp. (-12,260,600). The difference in length of hospital stay 0-5 days (66 patients) was Rp.(-85,504,600), length of hospital stay 6-10 days (41 patients) was Rp.(-107,463,600) and length of hospital stay (10 days (1 patient) was Rp.(-3,796,200). The real cost of hospital was greater than the INA CBGs tariff, thus causing a negative cost difference that can make financial loss to the hospitals.